Electrochemical sensor based on carbon nanotube decorated with manganese oxide nanoparticles for naphthalene determination - Alves, Ismael Carlos Braga; dos Santos, José Ribamar Nascimento; Marques, Edmar Pereira; Sousa, Janyeid Karla Castro; Beluomini, Maísa Azevedo [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Marques, Aldaléa Lopes Brandes (Springer Nature, 2023)
In this work, an electrochemical sensor was developed for the determination of naphthalene (NaP) in well water samples, based on a glass carbon electrode (GCE) modified as a nanocomposite of manganese oxides (MnOx) and COOH-functionalized multi-walled carbon nanotubes (MWCNT). The synthesis of MnOx nanoparticles was performed by the sol–gel method. The nanocomposite was obtained by mixing MnOx and MWCNT with the aid of ultrasound, followed by stirring for 24 h. Surface modification facilitated the electron transfer process through the MnOx/MWCNT/GCE composite, which was used as an electrochemical sensor. The sensor and its material were characterized by cyclic voltammetry (CV), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Important parameters influencing electrochemical sensor performance (pH, composite ratios) were investigated and optimized. The MnOx/MWCNT/GCE sensor showed a wide linear range of 2.0–16.0 μM, a detection limit of 0.5 μM and a quantification limit of 1.8 μM, in addition to satisfactory repeatability (RSD of 7.8%) and stability (900 s) in the determination of NaP. The determination of NaP in a sample of water from a gas station well using the proposed sensor showed results with recovery between 98.1 and 103.3%. The results obtained suggest that the MnOx/MWCNT/GCE electrode has great potential for application in the detection of NaP in well water. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Electrochemical sensor; MnOx; MWCNT; Nanocomposite; Naphthalene